Diabetes care and pregnancy outcomes for women with pregestational diabetes in Ireland. (March 2021) - Newman, C.; Egan, A.M.; Ahern, T.; Al-Kiyumi, M.; Balan, G.; Brassill, M.J.; Brosnan, E.; Carmody, L.; Clarke, H.; Coogan Kelly, C.; Culliney, L.; Davern, R.; et al.
Abstract: Aims: Pre-gestational diabetes mellitus (PGDM) is associated with adverse outcomes. We aimed to examine pregnancies affected by PGDM; report on these pregnancy outcomes and compare outcomes for patients with type 1 versus type 2 diabetes mellitus; compare our findings to published Irish and United Kingdom (UK) data and identify potential areas for improvement. Methods: Between 2016 and 2018 information on 679 pregnancies from 415 women with type 1 Diabetes Mellitus and 244 women with type 2 diabetes was analysed. Data was collected on maternal characteristics; pregnancy preparation; glycaemic control; pregnancy related complications; foetal and maternal outcomes; unscheduled hospitalisations; congenital anomalies and perinatal deaths. Results: Only 15.9% of women were adequately prepared for pregnancy. Significant deficits were identified in availability and attendance at pre-pregnancy clinic, use of folic acid, attaining appropriate glycaemic targets and appropriate retinal screening. The majority of pregnancies (n = 567, 83.5%) resulted in a live birth but the large number of infants born large for gestational age (LGA) (n = 280, 49.4%), born prematurely <37 weeks and requiring neonatal intensive care unit (NICU) admission continue to be significant issues. Conclusions: This retrospective cohort study identifies multiple targets for improvements in the provision of care to women with pre-gestational DM which are likely to translate into better pregnancy outcomes.